PENGEMBANGAN MEDIA KOMIK BERMUATAN CERITA RAKYAT SASAK DALAM PEMBELAJARAN MATEMATIKA MATERI OPERASI HITUNG BILANGAN BULAT SISWA KELAS IV SDN 1 AIKMEL - Alfianita; Moh Irawan Zain; Muhammad Sobri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a comic based learning media containing the Sasak folklore “Doyan Neda” for teaching integer arithmetic operations to fourth grade students at SDN 1 Aikmel, as well as to determine the validity, practicality, and effectiveness of the developed media. This research employed the Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The formative evaluation results showed that the comic media obtained a media expert validation score of 98.33% and a material expert validation score of 87.63%, both categorized as highly valid. The small group trial involving 7 students obtained a percentage score of 93.87%, categorized as highly feasible, while the large-group trial involving 18 students obtained a percentage score of 90.82%, categorized as highly feasible. Teacher responses toward the use of the media obtained a percentage score of 96.66%, categorized as highly practical. The effectiveness analysis through pretest and posttest results showed an improvement in students’ learning outcomes, with the average score increasing from 67.60 to 89.36, the learning mastery percentage increasing from 56% to 100%, and an N-gain score of 0.72, categorized as high. Based on these results, it can be concluded that the comic-based learning media containing the Sasak folklore “Doyan Neda” is valid, practical, and effective for use as a mathematics learning medium for integer arithmetic operations in fourth-grade elementary school, while also supporting the preservation of Sasak local culture through an ethnomathematics approach.